SLO—Needed by Corporations but not Required by Law - Wang, Pingping (Journal of Theory and Practice of Social Science, 2023)
The Social License to Operate initially originated in the mining industry. As economic activity has expanded, the concept has been enriched and different types have flourished. In the background of economic globalization, companies are having a deeper and deeper impact on all aspects of society and should also assume more social responsibility. Social license to operate is also a part of corporate social responsibility. This article analyzes the importance of social license to operate from different perspectives and why it has not yet been incorporated into the law.